Quantifying Digital Ulcers in Systemic Sclerosis: Reliability of Computer‐Assisted Planimetry in Measuring Lesion Size. Issue 3 (26th February 2018) - Simpson, V.; Hughes, M.; Wilkinson, J.; Herrick, A. L.; Dinsdale, G.
Abstract : Objective: Digital ulcers are a major problem in patients with systemic sclerosis (SSc), causing severe pain and impairment of hand function. In addition, digital ulcers heal slowly and sometimes become infected, which can lead to gangrene and necessitate amputation if appropriate intervention is not taken. A reliable, objective method for assessing digital ulcer healing or progression is needed in both the clinical and research arenas. This study was undertaken to compare 2 computer‐assisted planimetry methods of measurement of digital ulcer area on photographs (ellipse and freehand regions of interest [ROIs]), and to assess the reliability of photographic calibration and the 2 methods of area measurement. Methods: Photographs were taken of 107 digital ulcers in 36 patients with SSc spectrum disease. Three raters assessed the photographs. Custom software allowed raters to calibrate photograph dimensions and draw ellipse or freehand ROIs. The shapes and dimensions of the ROIs were saved for further analysis. Results: Calibration (by a single rater performing 5 repeats per image) produced an intraclass correlation coefficient (intrarater reliability) of 0.99. The mean ± SD areas of digital ulcers assessed using ellipse and freehand ROIs were 18.7 ± 20.2 mm 2 and 17.6 ± 19.3 mm 2, respectively. Intrarater and interrater reliability of the ellipse ROI were 0.97 and 0.77, respectively. For the freehand ROI, the intrarater and interrater reliability were 0.98 and 0.76, respectively. Conclusion: Our findings indicate that computer‐assisted planimetry methods applied to SSc‐related digital ulcers can be extremely reliable. Further work is needed to move toward applying these methods as outcome measures for clinical trials and in clinical settings.